Veränderungen des Mesoklimas durch Siedlungen im Raum Neustadt/Weinstraße - Geiger, Michael (ERDKUNDE, 1977)
This study covering a rurally-structured area is intended to complement what have become fairly numerous investigations of urban climates within cities and agglomeration areas. Making use of mobile instruments for measuring temperatures, minima and maxima thermometers and infra-red aerial photography, an investigation was carried out into the meso-climatic changes in the Weinstrasse region south of Neustadt. Corresponding with the size of settlement temperature rises of between 0.5°C and 5 °C were registered. Settlements lying within and in front of the valley funnels of the Pfalzerwald alter the natural circulation of air. They block the fresh air on arrival, and warm it up so that it no longer proceeds to the Rhine Plain. This interference with the bioclimatically highly significant local wind systems ought to be taken account of adequately in future measures adopted by regional and town planners. In this regard meso-climatic mapping represents a necessary investigation of underlying factors.